Does ecological marginality reflect physiological marginality in plants?. (3rd March 2020) - Abeli, Thomas; Ghitti, Michele; Sacchi, Roberto
Abstract: In the absence of barriers to dispersal, species' range limits should arise when physiological processes are compromised by unfavorable ecological conditions. This study aims to fill the knowledge gap on the role of physiology in determining plant species range limits. We developed the Physiological Marginality Hypothesis (PMH), a theoretical framework predicting that individuals in ecologically marginal populations are less physiologically efficient than those occurring at the ecological optimum. According to PMH, the probability to reach the optimal physiological efficiency is best shaped by a Gaussian function and curvilinear relationships should exist between physiological traits and ecological gradients. We conducted an analysis on plant physiology studies along altitudinal/latitudinal gradients to investigate which models best describe the relationship between the performance of a given physiological trait and the considered ecological gradients. Data from 54 cases (29 species) concerning photosynthesis, stomatal conductance, carbon isotope composition and photosynthetic water use efficiency were used. Overall, results support PMH in about 70% of cases, suggesting that ecologically marginal individuals can be physiologically less efficient than individuals occurring at the species ecological optimum. Physiology has an important causal role in shaping plant species distribution and further studies should focus on physiological processes at the ecological range edge.